1987
DOI: 10.1039/p19870000439
|View full text |Cite
|
Sign up to set email alerts
|

Propentdyopents [5-(2-oxo-2H-pyrrol-5-ylmethylene)pyrrol-2(5H)-ones] and related compounds. Part 1. On the structure of the propentdyopent–alkanol adducts

Abstract: First, the history of the structural problem of propentdyopents and their adducts (e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Two different approaches for the synthesis of octaethyl‐10‐thiacorrole 1 have been devised: the MacDonald‐type [2+2] condensation of tetraethyl‐2,2′‐bipyrrole 2 18 and bis(3,4‐diethyl‐5‐formylpyrrole)sulfide 4 , and the copper(II)‐templated macrocyclization of dibromodipyrrin 5 19 in the presence of sodium sulfide,12d followed by reductive demetalation (Scheme ) 20. The former pathway produces the desired macrocycle in an acceptable 29 % yield in the final step.…”
Section: Resultsmentioning
confidence: 99%
“…Two different approaches for the synthesis of octaethyl‐10‐thiacorrole 1 have been devised: the MacDonald‐type [2+2] condensation of tetraethyl‐2,2′‐bipyrrole 2 18 and bis(3,4‐diethyl‐5‐formylpyrrole)sulfide 4 , and the copper(II)‐templated macrocyclization of dibromodipyrrin 5 19 in the presence of sodium sulfide,12d followed by reductive demetalation (Scheme ) 20. The former pathway produces the desired macrocycle in an acceptable 29 % yield in the final step.…”
Section: Resultsmentioning
confidence: 99%
“…The first example of the use of lead tetraacetate to oxidize pyrrolic species was carried out by Bonnet and co‐workers in 1987 . This involved the treatment of dipyrrole diacid 90 to give dipyrrolinone species 91 in a yield of 13 % (Scheme ).…”
Section: Miscellaneous Methods For the Oxidation Of Pyrrolementioning
confidence: 99%
“…We have shown that tetraethyl propentdyopent Hpdp coordinates divalent transition metals and that the resulting homoleptic pseudo‐tetrahedral complexes [M(pdp) 2 , Scheme ] host stable ligand‐based radicals upon one‐electron reduction . Although convenient syntheses of dipyrrindione ligands were first reported in the 1980s, their boron coordination has not been investigated to the best of our knowledge. Herein, we sought to combine the ability of the dipyrrindione moiety to act as a redox‐active ligand with the emission properties of BODIPY analogs to afford a novel redox‐switchable fluorophore.…”
Section: Introductionmentioning
confidence: 99%